CFD simulation for optimizing flow dynamics in a bioelectrochemically enhanced single-chamber anaerobic digester - Feilner, Stefanie; Espejo, Marina; Garcia, M.; Molognoni, D.; Borràs, E.; Herkendell, Katharina (International Journal of Thermofluids, 2025)
The combination of anaerobic digestion (AD) and bioelectrochemical systems (BES) for improved biogas production makes a significant contribution to the conversion of organic waste materials into a usable, renewable energy source. This study employs computational fluid dynamics (CFD) to examine the performance of a bioelectrochemically enhanced single-chamber anaerobic digester (AD-BES). Flow conditions in a laboratory-scale stirred tank reactor are compared with those in an identical AD-BES reactor equipped with carbon fiber brush electrodes. Two configurations of the BES reactor, AD-BES-1 and AD-BES-2, were examined. The overarching aim of the analysis is to develop suitable fluid dynamic models for the simulation of the AD-BES reactor system. Particular emphasis is placed on modeling the turbulence and the rotational movement of the stirrer. With a realistic representation of the reactor system, the influence of the electrodes on the operating dynamics of the reactor, the mixing behavior and the formation of dead zones can be described and optimized. The simulation results were validated with experimental tests in an acrylic glass model reactor. Operating the included stirrer at 200 and 300 revolutions per minute (rpm) reveals that, with higher rotational speed the extension of dead zones is decreasing. The brush electrodes significantly influence the flow patterns, acting as obstacles. The arrangement of the electrodes determines the extent of the dead zones that occur between them and the reactor wall. In presence of the electrodes, the radial component of the flow velocity is decreasing, while the axial component is increasing.
CRIS-Team Scopus Importer:2025-10-16
Keywords: Anaerobic digestion; Bioelectrochemical system for energy storage; Biomethane; Computational fluid dynamics